Vestibular stimulation improves insight into illness in schizophrenia spectrum disorders. (May 2017) - Gerretsen, Philip; Pothier, David D.; Falls, Carolyn; Armstrong, Maxine; Balakumar, Thushanthi; Uchida, Hiroyuki; Mamo, David C.; Pollock, Bruce G.; Graff-Guerrero, Ariel
Abstract: Impaired insight into illness (IMP-INS) is common among individuals with schizophrenia spectrum disorders (SSD), contributing to medication nonadherence and poor clinical outcomes. Caloric vestibular simulation (CVS) is typically used to assess peripheral vestibular system function. Left cold CVS is also a transiently effective treatment for IMP-INS and hemineglect secondary to right brain hemisphere stroke, and possibly for IMP-INS and mood stabilization in patients with SSD. Participants with SSD and moderate-to-severe IMP-INS participated in an exploratory double blind, crossover, randomized controlled study of the effects of CVS on IMP-INS. Participants sequentially received all experimental conditions—left cold (4 °C), right cold, and body temperature/sham CVS—in a random order. Repeated measures ANOVA were performed to compare changes in IMP-INS, mood and positive symptom severity pre and 30 min post CVS. A significant interaction was found between CVS condition, time, and body temperature nystagmus peak slow phase velocity (PSPV) for IMP-INS, indicating that single session left cold CVS transiently improved IMP-INS while right cold CVS may have worsened IMP-INS, particularly in participants with greater vestibular reactivity (i.e. higher PSPV) to body temperature CVS. The procedure's effectiveness is attributed to stimulation of underactive right hemisphere circuits via vestibular nuclei projections to the contralateral hemisphere. Highlights: Single session left cold (4 °C) caloric vestibular stimulation (CVS) transiently improved impaired insight into illness (IMP-INS) while right cold CVS appeared to worsen IMP-INS, particularly in participants with greater vestibular reactivity to body temperature CVS. The procedure's effectiveness for IMP-INS in schizophrenia and other conditions that feature IMP-INS (e.g. stroke) is attributed to stimulation of underactive right hemisphere circuits via vestibular nuclei projections to the contralateral hemisphere. Future studies in schizophrenia spectrum disorders should consider: (1) multi-session designs (e.g. 10 consecutive days) to determine if repeated CVS can lead to sustained improvement in IMP-INS; and (2) other methods of vestibular stimulation, such as galvanic vestibular stimulation or air caloric vestibular stimulation, to determine if results are replicable across treatment approaches.